Ceramic bricks using pistachio shells as controlled porosity former - Nancy Quaranta; Marta Caligaris; Miguel Unsen; Hugo López; Gisela Pelozo; Adrián Cristóbal (Journal of Building Materials and Structures)
The present work studies the use of pistachio shells as a porosity-forming raw material in the manufacture of ceramic bricks. It focuses on the characteristics of the ceramic pieces obtained with different residual biomass contents (from 5 to 20% by volume). The specimens were shaped by uniaxial pressure of 25 MPa, and then were treated at 950°C for 3h. Based on the results obtained it is possible to conclude that the use of this residual biomass, as a pore former in the ceramic industry is feasible. The proportion of added biomass that generates the best characteristics and properties in the final product is 10%. Up to this percentage of aggregate, ceramic pieces with very good macroscopic and microscopic characteristics are obtained, with porosity and flexural strength values that meet market requirements for this type of product. Optical microscopy technique has been used to carry out a detailed analysis of the shape and size of the formed pores, which is a specific objective of this work. It has been observed that for contents of 5 and 10% biomass, the shape of pores is similar to the shape of the particles of added pistachio shells, while for higher contents (15 and 20%) it is different with elongated characteristics. In relation with the size of the pores, at lower contents is around 60% of the original particles size, and for the higher percentages of biomass, they are larger, indicating that agglomerates of particles are formed and when combusted, produce that porosity characteristics.